Characterization of the role of spatial proximity of DNA double-strand breaks in the formation of CRISPR-Cas9-induced large structural variations - Dahl-Jessen, Mikkel; Terkelsen, Thorkild; Bak, Rasmus O.; Jensen, Uffe Birk (Genome Research, 2025)
Structural variations (SVs) play important roles in genetic diversity, evolution, and carcinogenesis and are, as such, important for human health. However, it remains unclear how spatial proximity of double-strand breaks (DSBs) affects the formation of SVs. To investigate if spatial proximity between two DSBs affects DNA repair, we used data from 3C experiments (Hi-C, ChIA-PET, and ChIP-seq) to identify highly interacting loci on six different chromosomes. The target regions correlate with the borders of megabase-sized topologically associated domains (TADs), and we used CRISPR-Cas9 nuclease and pairs of single guide RNAs (sgRNAs) against these targets to generate DSBs in both K562 cells and H9 human embryonic stem cells (hESCs). Droplet digital PCR (ddPCR) was used to quantify the resulting recombination events, and high-throughput sequencing was used to analyze the chimeric junctions created between the two DSBs. We observe a significantly higher formation frequency of deletions and inversions with DSBs in proximity compared with deletions and inversions with DSBs not in proximity in K562 cells. Additionally, our results suggest that DSB proximity may affect the ligation of chimeric deletion junctions. Taken together, spatial proximity between DSBs is a significant predictor of large-scale deletion and inversion frequency induced by CRISPR-Cas9 in K562 cells. This finding has implications for understanding SVs in the human genome and for the future application of CRISPR-Cas9 in gene editing and the modeling of rare SVs.